Surface Roughness and Sliding Mechanics of Aesthetic Composites Brackets and Archwires: SEM-Profilometry Study - Sarder Sadique (International Journal of Supply Chain Management, 2016)
Objective: The purpose of this biomechanical study is to evaluate the surface topography (ST), surface roughness (SR), and hardness of available brackets/archwires including developed aesthetic polymer matrix composites (PMC) archwire and bracket (braided). Those are important determinants for the effectiveness of archwire-guided tooth movement. Materials and Methods: The present study characterizes and compares stainless steel (SS) developed PMC archwires and SS, ceramics, composite developed PMC brackets for ST, SR and hardness with respect to (w.r.t.) frictional force. Archwires are slid against the slots (contact flats) of brackets in tensile tester. Statistical analysis is performed with confidence level (p 0.05) for frictional force SR and hardness of SS archwires are analyzed as well. Detailed wear studied were performed by SEM. Results: The roughness average (Ra) and correlation coefficient (r) are expressed as the mean. Significant positive correlations (p 0.05) are observed. Identical hardness (580-600 kg/mm2) of SS archwires for different shapes are recorded except composite archwire. SEM results show that the ST of brackets and archwires varies among as-received and after sliding. Conclusions: Transcend (PCA) is the roughest brackets while the SS (SRO-AW) and aesthetic PMC archwires are the roughest archwires. Keywords Biomechanics (sliding), Aesthetic PMC Composites, Surface Roughness, Surface topography, Surface hardness.